1997
DOI: 10.1073/pnas.94.26.14798
|View full text |Cite
|
Sign up to set email alerts
|

A sensory brain map for each behavior?

Abstract: Multiple brain maps are commonly found in virtually every vertebrate sensory system. Although their functional significance is generally relatively little understood, they seem to specialize in processing distinct sensory parameters. Nevertheless, to yield the stimulus features that ultimately elicit the adaptive behavior, it appears that information streams have to be combined across maps. Results from current lesion experiments in the electrosensory system, however, suggest an alternative possibility. Inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 38 publications
4
72
0
Order By: Relevance
“…Previous studies have shown important differences in tuning between pyramidal cells of the different segments (Shumway, 1989a): pyramidal cells of the CMS/CLS/LS segments are tuned to low, mid, and high frequencies, respectively. This suggests a specific function for each segment, which has been partially verified through behavioural experiments (Metzner and Juranek, 1997). The mechanisms underlying differential tuning across the segments are still unclear.…”
Section: Pyramidal Cell Frequency Tuningmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have shown important differences in tuning between pyramidal cells of the different segments (Shumway, 1989a): pyramidal cells of the CMS/CLS/LS segments are tuned to low, mid, and high frequencies, respectively. This suggests a specific function for each segment, which has been partially verified through behavioural experiments (Metzner and Juranek, 1997). The mechanisms underlying differential tuning across the segments are still unclear.…”
Section: Pyramidal Cell Frequency Tuningmentioning
confidence: 76%
“…This burst mechanism has been shown to be controlled by a variety of intrinsic membrane conductances including persistent sodium currents and high-threshold potassium channels (Ellis et al, 2007b;Fernandez et al, 2005a;Mehaffey et al, 2006;Noonan et al, 2003;Rashid et al, 2001a,b). As channel densities have been shown to vary across the different tuberous maps (Deng et al, 2005;Smith et al, 2006), they may contribute to map-specific computations including frequency selectivity (Metzner and Juranek, 1997;Shumway, 1989a). Furthermore, synaptic input from feedback pathways can have a significant impact on burst firing (Bastian and Nguyenkim, 2001;Chacron and Bastian, 2008;Chacron et al, 2005a;Mehaffey et al, 2007Mehaffey et al, , 2008a.…”
Section: Regulation Of Pyramidal Cell Burstingmentioning
confidence: 99%
“…These make synaptic contact unto pyramidal cells within the hindbrain electrosensory lateral line lobe (ELL) which is composed of three parallel maps of the body surface (Shumway 1989;Krahe et al 2008) that are essential for proper sensory processing of natural stimuli (Metzner and Juranek 1997). The physiological responses of pyramidal cells within the three maps show important differences and have been well characterized both in vivo (Bastian et al 2002;Chacron et al 2003;Bastian et al 2004;Chacron et al 2005a, c;Chacron 2006;Chacron et al 2007;Chacron and Bastian 2008;Chacron et al 2009;Toporikova and Chacron 2009;Avila Akerberg et al 2010) and in vitro (Berman and Maler 1999;Oswald et al 2004;Ellis et al 2007a, b;Oswald et al 2007;Mehaffey et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The ensemble of premotor neurons encoding identity and location of an external object and triggering an innate response to that object has been referred to in the ethological literature as a "command releasing system" (Ewert, 1987). Such a system may be exclusively dedicated to a particular behavior, although it is debated whether this is a general feature of CNS organization (Metzner and Juranek, 1997;Edwards et al, 1999;Kupfermann and Weiss, 2001;Sewards and Sewards, 2002).…”
Section: Introductionmentioning
confidence: 99%